(untitled) (Bangladesh Journal of Medical Biochemistry, 2014)
Peroxidase enzyme was isolated and purified from the pulp of disease infected ripen papaya of local variety by 90% ammonium sulphate precipitation, chromatography on DEAEcellulose followed by hydrophobic chromatography on Phenyl Sepharose CL-4B and the purifications achieved was about 7.2 fold with 2.5% recovery. The purified enzyme was homogeneous as judged by polyacrylamide slab gel electrophoresis. The purified enzyme had a Mr of about 55,000 and 50 000 as determined by gel filtration on Sephadex G-100 and SDS-PAGE, respectively. The molecular mass of the enzyme was found to be very similar under both reducing and non-reducing conditions indicating that the enzyme contains no subunit. The enzyme has the following characteristics: pH optima at 6.0, temperature optima around 38°C, enzyme activity was found to be strongly inhibited in the presence of potassium cyanide and Fe+2 while the activity was found to be remarkably increased in the presence of ammonium sulphate. The Km value for the peroxidase obtained with pyrogallol as substrate was 0.027 mM. DOI: http://dx.doi.org/10.3329/bjmb.v6i2.17643 Bangladesh J Med Biochem 2013; 6(2): 49-57